Working with offenders (Research highlights in social work, 1996)
Significant changes have occurred in recent years in the nature and delivery of social work services to offenders and their families. Working with Offenders considers the implications for policy and practice of research which has focused upon a range of social work activities including assessment; intensive probation programmes; community service; reparation and mediation; social work with prisoners; work with sex offenders. It also considers more general issues of effectiveness, race and gender and locates recent developments in practice in the context of the broader policy changes in social work and criminal justice which have evolved over the last few years.